2020
DOI: 10.1007/s00404-020-05859-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic findings in miscarriages and their relation to the number of previous miscarriages

Abstract: Purpose Early pregnancy loss leads to a devastating situation for many couples. Genetic disorders found in the pregnancy tissue are a frequent cause of miscarriages. It is unclear whether maternal age or previous miscarriages are associated with a higher chromosomal anomaly rate. This study aimed to determine the cytogenetical distribution of chromosomal disorders in couples after one or more previous miscarriages as well as the influence of maternal age. Methods 406 fetal tissue samples obtained after sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…Advanced maternal age is related to an increased incidence of meiotic errors due to the extended period of oocyte meiotic arrest before ovulation [ 28 , 29 ]. The risk of cytogenetic errors was reported to be significantly higher in women over 40 years old [ 30 , 31 ]. There seems to be conflicting data on the frequency of chromosome abnormalities in sporadic miscarriages, as opposed to recurrent pregnancy loss (RPL), with some reports claiming that such abnormalities occur less often in RPL, and others reporting no correlation [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced maternal age is related to an increased incidence of meiotic errors due to the extended period of oocyte meiotic arrest before ovulation [ 28 , 29 ]. The risk of cytogenetic errors was reported to be significantly higher in women over 40 years old [ 30 , 31 ]. There seems to be conflicting data on the frequency of chromosome abnormalities in sporadic miscarriages, as opposed to recurrent pregnancy loss (RPL), with some reports claiming that such abnormalities occur less often in RPL, and others reporting no correlation [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced maternal age (≥ 35 ) is a well-known independent factor associated with the frequencies of cytogenetic abnormalities in early miscarriages [1,12,14]. In this study, the frequencies of abnormal karyotype in women aged up to 30 years, between 30 and 34 years, as well as between 35 and 39 were comparable, while the frequency was signi cantly higher in women ≥ 40 years old.…”
Section: Discussionmentioning
confidence: 51%
“…The most frequent cause of miscarriage is chromosomal abnormality. Almost 50 years of cytogenetic studies of spontaneous abortions have demonstrated abnormality rates of around 50–60% [ 10 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Trisomies are the most frequently detected anomalies (58–61%), followed by monosomy X (8–13%), polyploidies (2–13%), and structural anomalies (7–9%) [ 11 , 12 , 41 ].…”
Section: Genetic Causes Of Miscarriagementioning
confidence: 99%
“…Aneuploidy, the presence of an abnormal number of chromosomes, is thought to be a major cause of human first-trimester pregnancy loss [ 11 , 13 , 14 , 44 , 45 , 46 , 48 , 173 , 174 ]. Aneuploidy rates are remarkably high in early human embryos, with more than 50% of IVF embryos diagnosed as aneuploid, including those from young, fertile couples [ 175 , 176 , 177 ].…”
Section: Stem Cell-based Studies Of Chromosomal Aneuploidy and Mosaic...mentioning
confidence: 99%